Synthesis of Stereoselectively Functionalized Silacyclopentanes - Igawa, Kazunobu; Kuroo, Akihiro; Yoshihiro, Daisuke; Yamanaka, Yuki; Tomooka, Katsuhiko (Synlett, 2017)
An efficient approach to a variety of chiral silacyclopentanes having silicon stereogenic center based on the stereospecific transformations of C4 carbon stereogenic center of silacyclopentenols by Mitsunobu reaction or Tsuji–Trost reaction has been developed. The thus obtained substitution products can be converted into novel silacyclopentane triols, amines, and carboxylic acids in stereospecific manner.
Keywords: asymmetric synthesis; chiral silicon molecule; silacyclopentanes; Mitsunobu reaction; Tsuji–Trost reaction